THE CORRELATION BETWEEN APGAR SCORE AND GESTATIONAL AGE WITH NEONATAL SEPSIS AND ASSOCIATED MORTALITY - Nabila Annisa Harum; Martono Tri Utomo; Aditiawarman -; Prastiya Indra Gunawan (JURNAL WIDYA MEDIKA, 2021)
Background: Neonatal sepsis is increasingly recognized as an important global health problem that challenges neonatal survival. In 2018, sepsis caused approximately 15% of all neonatal deaths worldwide. Recent data regarding preterm birth and low Apgar score as risk factors for neonatal sepsis-related death have not been reported in Indonesia. Methods: This was a case-control study conducted in Dr.Soetomo General Hospital. A case group was obtained from medical records by a total sampling of all neonates diagnosed with neonatal sepsis in 2019, and a control group of non-neonatal sepsis cases was taken by random sampling. Chi-square test and logistic regression were used to analyze the data. Results: Statistical analysis showed a significant correlation between one and five-minute Apgar score